2015
DOI: 10.1098/rspb.2014.1745
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relatedness does not predict competition and co-occurrence in natural or experimental communities of green algae

Abstract: The competition-relatedness hypothesis (CRH) predicts that the strength of competition is the strongest among closely related species and decreases as species become less related. This hypothesis is based on the assumption that common ancestry causes close relatives to share biological traits that lead to greater ecological similarity. Although intuitively appealing, the extent to which phylogeny can predict competition and co-occurrence among species has only recently been rigorously tested, with mixed result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 78 publications
(125 reference statements)
3
31
1
Order By: Relevance
“…In contrast, other studies have found no relationship between phylogenetic relatedness and strength of competition (Alexandrou et al 2015;Fritschie et al 2014;Venail et al 2014). These studies, however, were performed under relatively benign environments relative to our study.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In contrast, other studies have found no relationship between phylogenetic relatedness and strength of competition (Alexandrou et al 2015;Fritschie et al 2014;Venail et al 2014). These studies, however, were performed under relatively benign environments relative to our study.…”
Section: Discussioncontrasting
confidence: 46%
“…However, support for the PLSH is equivocal (Alexandrou et al 2015;Cahill et al 2008;Fritschie et al 2014;Narwani et al 2013;Venail et al 2014). For example, both Cahill et al (2008) and Verdu et al (2012) performed meta-analyses on the relationships between phylogenetic distances and plant species interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, a consensus has not been reached on whether low or high phylogenetic relatedness could promote invasions [1, 5–10]. On the one hand competition-relatedness hypothesis, [9] suggests that the competitive exclusion of closely related species restricts invasion, for example because of overlapping resource use, as well as shared predators, herbivores, and pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess whether PD determines the level of competition experienced by members of a multi-species community, we ran a laboratory mesocosm experiment in which we varied the PD represented by eight common species of green algae, and then assessed the competitive response of each species to additions or deletions of the other taxa grown in polyculture. We used a data-rich molecular phylogeny of 59 green algae species (Alexandrou et al 2015) to determine the relatedness of algal species comprising each community. We measured phylogenetic distance from a focal species to the resident community as the average PD between a focal species and each other species present in the community.…”
Section: Introductionmentioning
confidence: 99%